Prospective multicenter international study on the outcomes of a newly developed self‐approximating lumen‐apposing metallic stent for drainage of pancreatic fluid collections and endoscopic necrosectomy. Issue 3 (30th August 2019) - Teoh, Anthony Yuen Bun; Bapaye, Amol; Lakhtakia, Sundeep; Ratanachu, Thawee; Reknimitr, Rungsun; Chan, Shannon Melissa; Choi, Hyun Jong; Gadhikar, Harshal P.; Kongkam, Pradermchai; Korrapati, Sravan Kumar; Lee, Yun Nah; Medarapalem, Jahangeer; et al.
Abstract : Background: A novel self‐approximating lumen‐apposing metallic stent (LAMS; Niti‐S Spaxus, Taewoong Medical, Gyeonggi‐do, Korea) has recently become available. The aim of the present study was to evaluate the outcomes for drainage of pancreatic fluid collections (PFC). Methods: This was a prospective international multicentered study conducted in six high‐volume institutions across Asia. Consecutive patients suffering from pancreatic pseudocyst or walled‐off pancreatic necrosis (WOPN) requiring endoscopic ultrasonography‐guided drainage were recruited. Outcomes included technical and clinical success, adverse events, procedural events, interventions through the stent and recurrence rates. Results: Between August 2016 and November 2017, 59 patients were recruited to this study. Thirty‐nine patients (66.1%) had WOPN and mean (SD) size of PFC was 11.5 (5.1) cm. Technical and clinical success rates were 100%. Mean (SD) procedural time was 35.0 (17.2) minutes. Sixteen‐millimeter stents were used in 66.1% of the patients. Fifty‐four sessions of necrosectomy were carried out with the stent in situ in 17 patients. Stent‐related adverse event (AE) rate was 6.8%. Three patients (5.1%) suffered from bleeding after stenting and one required angiographic embolization. Two patients (3.4%) suffered from recurrence during a mean (SD) follow‐up time of 325.6 (355.5) days. There were no differences in outcomes between those with pseudocysts or WOPN except for the duration of hospital stay ( P = 0.012). Conclusion: Use of a self‐approximating LAMS for drainage of PFC was safe and effective. Endoscopic necrosectomy could be carried out through the stent with ease. The device was associated with a low rate of stent‐related AE.